Leadership Personality and Social Dis-integration in Somalia - Hussein, Abdisamad Hassan (Asian Research Journal of Arts & Social Sciences, 2019)
The study seeks to explore the impact of leadership personalities of previous Somali political leaders on social integration. As Somalia now transit into post conflict reconstruction, there is the need to explore how previous flaws in leadership personalities resulted into social disintegration of the Somali society. To achieve this objective, qualitative interviews were held with 13 respondents across Somali elite in Mogadishu. Using the Big Five personality framework, the results revealed that previous Somali leadership personalities were deeply flawed due to colonial legacy and influence of clannism. In addition, fear of losing and retaining power at all cost instituted clannism as a means on obtaining and retaining political power, thereby compromising unity and social integration. The result also depicted that a significant number of Somali leaders were generally low in conscientiousness as a necessary leadership quality within the Big Five framework. The study maintains that the ongoing post-conflict reconstruction is unlikely to succeed unless leadership personality adapts properly to the prevailing situation of social integration. Moreover, the study recommends that leadership in Somalia should prioritize the restoration of social trust so that Somalia’s reconstruction process can succeed